(untitled) (Progressive Agriculture, 2021)
The poultry selling and processing practices followed in the poultry wet markets of Bangladesh are always being overlooked unknowingly. The research was conducted to observe the existing scenario of poultry selling and processing practices at the selected wet markets located in the Gazipur City Corporation of Bangladesh. A total of 43 poultry selling shops were randomly selected and interviewed using a semi-structured questionnaire. It was surprising to observe the absence of female personnel and involvement of few (6.9%) people over the age of 50 years in the wet markets. All the persons engaged in poultry selling and processing had no institutional training. The shops found to be abstained from following some important practices such as feed withdrawal period, isolation of diseased birds, ante and post mortem inspection. The proper bleeding time (1-2) min was recorded in 58.2% cases. The killing cone was recognized as the best device in terms bleeding time. The 72.1% of the outlets never cleaned the carcass prior to deliver the customers. The absence of ante- and post-mortem inspections may cause a great threat of disease outbreak. Taken together, the poultry selling and processing practices followed in the wet market needs to be assessed carefully to deliver safe and quality meat to the customers. In addition, organizing basic training on pre-slaughter management and processing for both seller and processor and also ensuring the regular ante- and post- mortem inspection could improve the present situation in order to produce quality poultry meat. Progressive Agriculture 31 (3): 205-217, 2020